(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
The interaction of analginum anion with dye of diaminoksantene raw rhodamine C has been studied. Formed ionic associate could be extracted once trough (R=0.975) by dichlorethane-amilacetate (1:4) binary mixture from solutions pH 1 to 1.0 N HCl and rhodamine C is 3.7·10-4–4.6·10-4M. The range of determined concentration of analginum is 2.4·10-5–l.44·10-4 M. The molar coefficient of extraction ε_565 = 4.2·104 L·mol-1·cm-1. The method was used for determining small amounts of analginum in spazmalgonum, baralginum and pentalginum.